2015
DOI: 10.1038/ncomms9671
|View full text |Cite
|
Sign up to set email alerts
|

Physical nanoscale conduit-mediated communication between tumour cells and the endothelium modulates endothelial phenotype

Abstract: Metastasis is a major cause of mortality and remains a hurdle in the search for a cure for cancer. Not much is known about metastatic cancer cells and endothelial cross-talk, which occurs at multiple stages during metastasis. Here we report a dynamic regulation of the endothelium by cancer cells through the formation of nanoscale intercellular membrane bridges, which act as physical conduits for transfer of microRNAs. The communication between the tumour cell and the endothelium upregulates markers associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
90
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(94 citation statements)
references
References 62 publications
(81 reference statements)
4
90
0
Order By: Relevance
“…The biogenesis and release of exosomes could be impaired by dimethyl amiloride and inactivation of the small GTP‐binding protein ARF6, respectively . Additionally, the formation of TnTs could be inhibited by mTOR signalling inhibitors metformin and everolimus, and cytoskeletal inhibitors docetaxel and latrunculin A as previously reported . Second, post‐transcriptional RNA interference by HLA‐G‐specific miRNAs (such as miR‐148, miR‐152, miR‐548q and miR‐628‐5p) has been demonstrated to reduce HLA‐G expression and recover NK cell lysis of tumor cells .…”
Section: Translational Implications Of the Intercellular Transfer Of mentioning
confidence: 67%
See 1 more Smart Citation
“…The biogenesis and release of exosomes could be impaired by dimethyl amiloride and inactivation of the small GTP‐binding protein ARF6, respectively . Additionally, the formation of TnTs could be inhibited by mTOR signalling inhibitors metformin and everolimus, and cytoskeletal inhibitors docetaxel and latrunculin A as previously reported . Second, post‐transcriptional RNA interference by HLA‐G‐specific miRNAs (such as miR‐148, miR‐152, miR‐548q and miR‐628‐5p) has been demonstrated to reduce HLA‐G expression and recover NK cell lysis of tumor cells .…”
Section: Translational Implications Of the Intercellular Transfer Of mentioning
confidence: 67%
“…70,71 Additionally, the formation of TnTs could be inhibited by mTOR signalling inhibitors metformin and everolimus, and cytoskeletal inhibitors docetaxel and latrunculin A as previously reported. 72,73 Second, post-transcriptional RNA interference by HLA-G-specific miRNAs (such as miR-148, miR-152, miR-548q and miR-628-5p) has been demonstrated to reduce HLA-G expression and recover NK cell lysis of tumor cells. 74 Third, the masking of either HLA-G or receptor ILTs with specific blocking antibodies could be a promising strategy for HLA-G/ILTs-based target therapy.…”
Section: Translational Implications Of the Intercellular Transfer Of mentioning
confidence: 99%
“…1) include direct cell-to-cell contact with both ligand-receptor signaling and transport of small molecules, including miRNAs, across gap junctions [14]. Cells separated by short distances can also pass macromolecules, organelles, and nuclei through “tunneling” nanotubes [15], and microtubes [16]. …”
Section: Ev Subtypes and Why Vesicles Are Unique Vehiclesmentioning
confidence: 99%
“…Another interesting possibility, entirely speculative at this point, is transport through micro- or nanotubes. It has been shown that tumor cells form tube-like conduits among themselves and to endothelial cells, and that that cellular macromolecules can be transported from one cell to another through these conduits [29,30,31]. The transport though these tube conduits has been found to be more effective than exosome transport, at least over short distances [30], so this mechanism could explain the effectiveness and speed of the trans-tissue transport by the CendR pathway [25].…”
Section: The Cendr Pathwaymentioning
confidence: 99%